2018
DOI: 10.3390/ma11122532
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Trauma Intensity during Surgical Bone Procedures Using NF-κB Expression Levels as a Stress Sensor: An Experimental Study in a Wistar Rat Model

Abstract: Aim and objectives: It is well known that the transcription factor NF-κB regulates multiple aspects of innate and adaptive immune functions and functions as a pivotal mediator of inflammatory responses. In the present study, we evaluated the trauma generated (inflammatory reaction) after osteotomy bone surgical procedures and placement of implants in the femoral cortical bone of Wistar rats. Surgical stress was evaluated measuring the release and activation of the NF-κB factor. Materials and Methods: Rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The intensity of surgical trauma during implant procedures maneuvers may vary during the drilling or insertion of the implant, as was demonstrated in our previous studies where NF-kB, which is a transcription factor involved in controlling the expression of several genes linked to the inflammatory response, was measured [30]. The excess trauma caused by the inadequate drilling process or the excess compression of the bone tissue during implant installation was reported in some studies [20,31,32].…”
Section: Discussionmentioning
confidence: 82%
“…The intensity of surgical trauma during implant procedures maneuvers may vary during the drilling or insertion of the implant, as was demonstrated in our previous studies where NF-kB, which is a transcription factor involved in controlling the expression of several genes linked to the inflammatory response, was measured [30]. The excess trauma caused by the inadequate drilling process or the excess compression of the bone tissue during implant installation was reported in some studies [20,31,32].…”
Section: Discussionmentioning
confidence: 82%
“…Events related to implant installation, such as milling and implant insertion, promote different intensities of bone tissue trauma, which affect the inflammatory reaction. This intensity of the inflammatory response, promoted during the implant implantation surgery, was measured by the expression of the transcription factor NF-kB in previous studies performed by our group [36]. Other studies on the same theme have also shown that the excess trauma caused during milling or bone compression during implant insertion can negatively interfere with the healing process of this tissue [23,32,33].…”
Section: Plos Onementioning
confidence: 90%
“…The selected strategy was to locally provide microelements capable of interacting with the intra and extracellular environment, thus promoting a favorable environment, capable of promoting the repair of the injured target tissue, reducing local oxidative stress, providing favorable conditions for cellular respiration and promoting growth of the injured target tissue. Although unorthodox, this strategy has shown good results in preliminary studies carried out in laboratory animals [ [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%